WOUND HEALING CONCEPTS: CONTEMPORARY PRACTICES AND FUTURE PERSPECTIVES - FURTADO, SHARON C.; SRINIVASAN, BHARATH; ABRAHAM, SINDHU (International Journal of Applied Pharmaceutics, 2020)
The advancements in the development of wound dressings have seen tremendous growth in the past few decades. Wound healing approach has majorly shifted from dry healing to moist healing. There has been a significant advancement in our understanding of the underlying physiology involved in wound healing and the associated systemic factors having a direct or indirect influence on the healing. This has resulted in the development of wound dressings designed to treat specific types of wounds. The present review discusses the physiology of wound healing, followed by different factors that contribute to healing. The advancements in wound dressings with their merits and limitations, newer approaches in wound care i.e., hyperbaric oxygen, negative pressure therapy, skin substitutes and role of growth factors in wound healing, have been highlighted. In addition, more recent approaches for effective wound care like smart devices with sensing, reporting and responding functions are discussed.